Profile of childhood hearing loss in the Western Cape, South Africa. (October 2020) - Kuschke, Silva; Swanepoel, De Wet; le Roux, Talita; Strauss, Susan
Abstract: Objectives: To describe the nature, associated risk factors and age of diagnosis for childhood hearing loss in a South African cohort from the Western Cape Province. Methods: A retrospective review of clinical data from children under six years of age with confirmed hearing loss at Red Cross War Memorial Children's Hospital (RCWMCH) was conducted between 1 January 2019 and 31 July 2019. Data collected included demographic information, type and degree of hearing loss, documented risk factors associated with hearing loss, and age of suspicion and diagnosis of hearing loss. Results: The study sample included 240 children with hearing loss, with a mean age of 42 months (21.8 SD; range 2–72). More than two thirds (68.3%) of the children presented with bilateral hearing loss. The majority presented with conductive hearing loss (64.6%), followed by sensorineural (28.7%) and mixed hearing loss (3.3%) or auditory neuropathy spectrum disorder (3.3%). More than half (51.8%) of the bilateral sensorineural hearing losses were of a profound degree. The most prominent risk factor for conductive hearing loss was otitis media, for sensorineural hearing loss it was a family history of childhood hearing loss, and for auditory neuropathy spectrum disorder it was hyperbilirubinaemia. Approximately one third of patients (27.1%) with sensorineural hearing loss did not have any associated risk factors. The mean age of diagnosis of permanent congenital or early-onset hearing loss was 31.4 months (22.8 SD; range 2–72), with a mean delay of nine months (13.2 SD; range 0–60) between age of suspicion and diagnosis of hearing loss (n = 93). Conclusions: The large proportion of preventable hearing losses in this sample highlights the importance of maximising primary health care efforts to treat preventable causes timeously. Age of diagnosis of permanent congenital or early-onset hearing loss was severely delayed undermining prospects of positive outcomes through early intervention. Infant hearing screening services in the public health sector of South Africa should be prioritised alongside primary health care efforts to reduce preventable risks for hearing loss.